KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN DI SEKOLAH DASAR - Siti Habsari Pratiwi; Anggili Pratama; Dian Armanto; Anita Yus (Universitas Negeri Medan, 2023)
This study aims to determine the leadership style of the principal of a female elementary school at Public Elementary School 1 Paya Bujok Tunong, Langsa City, Aceh. This research was conducted using phenomenological and qualitative methods. The result of this study is that female elementary school principals have the ability to improve the quality of education significantly. Principals of female primary schools usually focus on teacher morale, mastery of technical skills, and high responsibility for the school organization. Women also have a good sense of control because they are detailed. The success of a woman as a leader is influenced by several factors. Dominant factors that influence women`s leadership, namely: mother (mother), seductress (attention sucker), pet (beloved child), and iron maiden (strong woman).